2023
DOI: 10.1021/acscatal.3c00388
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Effect of the Nickel–Silica Interface Promotes the Water–Gas Shift Reaction

Abstract: Silica is commonly considered an inert support, and limited research has been concentrated on its role in constructing active metal− (hydr)oxide interfaces. Herein, we found that modifying the surface of nickel with silica will significantly promote its catalytic performance toward the water−gas shift reaction (WGSR), and the well-fabricated Ni np @PS(H450) exhibits a WGSR rate of up to 725 ± 7 μmol CO g cat −1 s −1 at 350 °C, which is at the highest level compared with previously reported Ni-based catalysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The positive valence metal species on the surface of the used catalysts may be closely related to the formation of interface structures. 32,36 The XPS results also indicated that there were still positive valence Cu species on the surface of the used catalysts. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The positive valence metal species on the surface of the used catalysts may be closely related to the formation of interface structures. 32,36 The XPS results also indicated that there were still positive valence Cu species on the surface of the used catalysts. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5e). 32,36 Based on the above-mentioned results, the adsorption and activation capacity of the catalysts for reaction molecules were further explored. As shown in Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…In summary, regardless of the reaction pathways, fundamental factors controlling water dissociation and subsequent conversion are closely related to the geometric and electronic structures of the oxide supports and metal components in WGS catalysts . Strong interactions between the metal species and the support may promote the formation of unique interfacial sites for optimizing the catalytic performance for the WGS reaction. ,,, …”
Section: H2o As a Promotor Or Coreactant In Co Reactionsmentioning
confidence: 99%